Antagonistic Ability and Fungicide Tolerance of Rhizosphere Actinomycetes from the Hungayono Karst Ecosystem, Gorontalo - Nazifah R Adam; Yuliana Retnowati; Abubakar Sidik Katili; Novri Youla Kandowangko; Wirnangsi D. Uno (Biology, Medicine, & Natural Product Chemistry, 2026)
Actinomycetes show promise as biological control agents, reducing fungicide use in agriculture due to their bioactive compounds and ecological resilience. This study focused on the initial screening and ecological bioprospecting of actinomycetes from the Hungayono karst ecosystem in Gorontalo by determining their antagonistic activity against the pathogenic fungi Fusarium oxysporum and Neocosmospora solani, as well as their tolerance to the fungicides thiram and benomyl. Potential isolates were identified using molecular methods. Samples were collected from three locations. Rhizosphere soil samples were obtained from plant species: Alocasia macrorrhizos, Ficus microcarpa, and Acrostichum aureum L. Antagonistic activity against root-pathogenic fungi and tolerance to fungicides were used as initial screening criteria to assess their potential as biological control agents. This study successfully isolated 9 actinomycete isolates. The results showed that only 33% of the isolates exhibited inhibitory activity, with isolate RzAH-07 showing a moderate inhibition zone (5.22 mm) against Fusarium oxysporum and weak inhibition (4.18 mm) against Neocosmospora solani, while also demonstrating tolerance to the fungicide benomyl up to 1000 ppm. RzAH-07 was selected as the top candidate due to its two key advantages. Phylogenetic analysis based on 16S rRNA gene sequences indicates that RzAH-07 is closely related to the genus Streptomyces, with a similarity percentage ranging from 98.35% to 99.14% based on GenBank data.